Prevalência e fatores de risco para a infecção pelo Toxoplasma gondii em granjas de reprodutores suídeos certificados ou não da microregião de Toledo, PR, Brasil - Piassa, Franciele Rossandra; de Araújo, Jacqueline Baptista; da Rosa, Ronaldo César; Mattei, Rodrigo José; da Silva, Rodrigo Costa [UNESP]; Langoni, Helio [UNESP]; da Silva, Aristeu Vieira (My University, 2010)
Toxoplasma gondii infection has been diagnosed in pigs all over the world. Economical losses are generally related to reproductive disorders. Toxoplasma infection is also a matter of public health because tissue cysts of the parasite may remain in pork and pork products, and become sources of human infection. The objective of this study was to evaluate the frequency and risk factors associated with Toxoplasma infection in certified and non-certified pig breeding farms in the Toledo microregion, in the State of Paraná, Brazil which includes the cities of Toledo, Nova Santa Rosa, Sao José das Palmeiras and Sao Pedro do Iguaçu. Relative frequency of infection was 13.4%, independently of the type of farm. Logistic regression analysis showed that the following factors were associated with infection: absence of workers exclusive for each area of the farm, access of other animals to feeders and drinkers, lack of lids in drinkers, lack of rodent control measures, mean piglet number and weight at weaning per female.
Prevalence and risk factors for Toxoplasma gondii infection in certified and non-certified pig breeding farms in the Toledo microregion, PR, Brazil
Keywords: Logistic regression analysis; Prevalence; Risk factors; Swine; Toxoplasma gondii